Epidural steroid injections in the management of lumbar radiculitis - Ripon, M F T; Rahman, M M; Mondal, S; Dey, L C; Tipu, T M; Milon, O; Arefin, N; Rahman, M; Chowdhury, A (Journal of Dhaka National Medical College & Hospital, 2014)
Low back pain is a common problem in human mostly due to disc degenerative disease. By any means, disc disorders are a tremendous problem. Pain is associated with or without radiculopathy. One of the most common causes of low back pain is lumbar disc herniation. The treatment option for lumbar disc herniation /disc degenerative disease may be conservative, epidural injection and surgery. Epidural steroid injection is a one of the choice alternative to surgical intervention in the treatment of lumbar disc herniation. This study was determining the efficacy of epidural steroid injection in the treatment of the patient with symptomatic lumbar disc herniation. Pain relief was excellent 38(%), patient good response was seen in 20(%), patients, no significant pain relief in 10(%) patients. The goal is to reduce severe pain with or without radiculopathy, to decrease the need for oral analgesics, early return to normal activities and physical therapy programme. J. Dhaka National Med. Coll. Hos. 2014; 20 (02): 43-45